A SURVEY OF SEMANTIC PRIMITIVE ON AUGMENTOR: MORE” - Ni Putu Meri Dewi Pendit (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2020)
Some words are innately understood but cannot be expressed in simpler terms. They represent words or phrases that are used through practice but cannot be defined correctly. Those words cannot even be explained by other terms. This is called semantic primitive. The use of the word ‘more’ still has many meaning. Hence, this paper discusses about the semantic primitive on augmentor ‘more’.